E-Module of Chemistry Practicum Based on Cooperative Learning on Salt Hydrolysis Material to Improve Students' Scientific Literacy - Luthfiana, Airiza Dian; Hidayah, Rusly (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This research aims to determine the feasibility of the practicum e-module based on cooperative learning on salt hydrolysisi material. Feasibility can be viewed from the validity, practicality, and effectiveness. This research was carried out in class XII MIA 1 at SMAM 10 GKB with a total of 24 students. The research method used is the 4-D method.Â  This study used instruments in the form of validation sheets, student response questionnaires, and pretest posttest question sheets. Â To analyze the results of the scientific literacy test, a non parameteric test was used (Wilcoxon Test). The validity of the e-module has valid and very valid criteria, the content criteria obtained a percentage of 81.37%, language criteria obtained 83.33%, presentation criteria obtained 80.66%, and graphics criteria obtained 82.66%. Based on practicality, the content criteria obtained a response percentage of 87.33%, the presentation criteria obtained 86.78%, the graphic criteria obtained 97.50%, and the language criteria obtained 97.52%. Student activities have very practical criteria, because the percentage is 100% or it can be stated that all activities are carried out. Wilcoxon test results get the Asymp value. Sig. (2-tailed) of 0.000 (H0 is rejected). E-module of chemistry practicum based on cooperative learning on salt hydrolysis material can increase students' scientific literacy results so that it is effective to use.